Analisis Kebutuhan Kualitas Perangkat Lunak untuk Game Mobile Tantangan dan Solusi - Aulia, Dhafa; Padli Nasution, M.Irwan (Jurnal Sistem Informasi Galuh, 2025)
This article discusses Software Quality Requirements Analysis for Mobile Games. The rapid development of the mobile gaming industry has increased user expectations for software quality. This research aims to analyze the quality requirements of mobile gaming software and also identify common challenges in meeting these requirements. Through literature observations and case studies, this research presents several important quality aspects, such as performance, resolution, usability, and compatibility. Additionally, the study also identified challenges related to hardware, platform segmentation, and market momentum. Based on the analysis results, this research presents several solutions that can overcome these challenges, such as performance optimization, extensive testing, and response design. Therefore, it is hoped that this research can help mobile game developers to produce high quality products that are able to compete in the competitive game market.